Determinación de la calidad del agua mediante la comunidad de macroinvertebrados bentónicos en la subcuenca del río carrizal - Cedeño Relles, Andrea Valeria (2016)
Water quality was determined by benthic macroinvertebrates in the Carrizal sub-basin during the rainy season (March to April) and dry (July-August) 2016. For this six sampling stations were established along the river, where a stretch of 100 meters long and each station is evaluated, taking five subsamples. Using networks kick and Surber 1741 individuals belonging to 33 families and 6 orders of the class Insecta he was captured. The average diversity in this ecosystem, calculated with the Shannon-Weaver index and compared with the scheme Dorris and Wilhm and places it in the 1-3 range, which shows that the sub-basin has a moderate pollution. On the other hand, the EPT and BMWP, indexes agreed on the qualification of water Carrizal subbasin, showing a regular attribute of water according to the results in stations E1 "Quiroga," E5 "Estancillas" and E6 "Tosagua"; while stations E2 "Measles" E3 "Paradise" and E4 "Calceta" showed good quality. Three physical parameters (pH, DO and temperature) were evaluated. DO was positively correlated to BMWP but temperature, negatively correlated. The physical variables showed acceptable limits during both seasons. By application of biological index water quality in Carrizal River’s subbasin goes from good (2, 3 and 4 station) to low (station 5) caused by factors such as the damming of the river bed, removal of riparian vegetation, etc.